Dietary Patterns, Genetic Predisposition, and Cognitive Function in the UK Biobank. (7th June 2021) - Schulz, Christina-Alexandra; Weinhold, Leonie; Schmid, Matthias; Nöthlings, Ute; Nöthen, Marcus M
Abstract: Objectives: Elucidating the role of dietary intake in cognitive function, and neurodegenerative disease development is important for prevention. The Mediterranean diet has shown to be beneficial for cognitive function and prevention of neurodegenerative disease. Yet, evidence for other dietary patterns are inconclusive. Since heritability of cognitive functions is substantial, a beneficial diet might mitigate genetic disposition. Therefore, we investigate if dietary patterns are associated with general cognitive function, considering individual genetic disposition. This research has been conducted using the UK Biobank Resource. Methods: At baseline, participants reported the frequency of consumption of main foods via a dietary touchscreen questionnaire and filled in a verbal-numerical reasoning (VNR) test, which measures fluid intelligence. A diet score including 7 components: vegetables, fruit, fish, processed meat, unprocessed meat, whole grain, and refined grain was constructed. Participants were categorized into a low (0–1), intermediate (2–5), and high (6–7) diet score. A polygenic score (PGS), previously associated in GWAS with general cognitive function, was constructed. Participants were categorized into low (Quintile 1), intermediate (Q 2–4), and high (Q 5) PGS group. Linear regression was used to test whether the diet score associates with fluid intelligence, and to test if genetic predisposition modifies the association. Results: The mean diet score of the 104, 898 participants (46% male, mean age 57.1 (SD 8.0) years) was 3.9 (SD 1.4) points. In the VNR-test on average 6.1 (SD 2.1) questions were answered correctly. After multivariate adjustment a positive association between fluid intelligence and the PGS ( P  < 0.001), but no association between fluid intelligence and the diet score ( P  = 0.703) was observed. When stratified according to PGS groups, similar results were observed for the association between fluid intelligence and the diet score. Conclusions: No evidence was found that the investigated diet score was associated with fluid intelligence. As previously reported, genetic disposition was strongly associated with cognitive performance. Funding Sources: This work was partly supported by Diet–Body–Brain (DietBB), the Competence Cluster in Nutrition Research funded by the Federal Ministry of Education and Research (FKZ: 01EA1410A).